MEDICAMENTAL IMMUNOSUPRESSION IN EARLY AGE PEDIATRIC LIVER RECIPIENTS - S. V. Gautier; D. S. Mnatsakanyan (Вестник трансплантологии и искусственных органов)
The article presents analysis of scientific literature of the last 20 years about medicamental immunosupression in early age pediatric liver recipients in view of immune response characteristics and immunosuppressive drugs pharmacokinetics in such patients. The modern concept of immunosuppressive therapy protocol choice in pedia- tric liver recipients depending on complications development (nephrotoxicity, arterial hypertension and neuroto- xicity, the high risk of infectious complications, post-transplant proliferative disorders, metabolic and cosmetic side effects) is presented. Different opportunities of early steroid withdrawal, calcineurin inhibitor minimization in pediatric liver allograft recipients are covered.